Flavor violating $\ell_i$ decay into $\ell_j$ and a light gauge boson - Alejandro Ibarra, Marcela Marín, Pablo Roig (SciPost Physics Proceedings, 2025)
The $\ell_i→\ell_jχ$ decays, with $χ$ a boson associated to the $U(1)_χ$ symmetry, have not been described satisfactorily so far for light spin-one $χ$. In particular, observables exhibited an unphysical divergence in the limit of massless $χ$, associated to its longitudinal polarizations. Based on gauge symmetry, we show how to correct this issue. To this end, we consider two general models realizing the effective field theory description. Being the LFV generated either at tree level or at one loop, these processes are well behaved for light $m_χ$. We discuss the most salient phenomenological consequences and its relevance in the searches for this kind of decays.